Detection of Double-Stranded-Rna by Elisa and Dot Immunobinding Assay using an Antiserum to Synthetic Polynucleotides - Aramburu, Jose; Navas-Castillo, J.; Moreno, Pedro; Cambra, Mariano (2017)
An antiserum against polyinosinic-polycytidylic acid (In-Cn) was used to detect double-stranded RNA (dsRNA) by several serological techniques. DsRNA was readily detected by indirect ELISA (ELISA-I) and dot immunobinding assay (DIA). Addition of the antigen to poly-L-lysine-precoated plates and blocking with uncreamed milk powder allowed detection levels of 100 pg.ml-1 In-Cn by ELISA-I. Concentrations as low as 1 ng.ml-1 were detected by DIA using polyvinyliden difluoride (PVDF) membranes. Detection capacity with nitrocellulose membranes was 1000 times lower than with PVDF. ELISA-I and DIA enabled detection of dsRNA in enriched fractions from cucumber mosaic virus (CMV)- and citrus tristeza virus (CTV)-infected plants and from virus-infected Penicillium chrysogenum mycelium. These techniques showed similar or higher sensitivity for detection of dsRNA than separation by polyacrylamide gel electrophoresis and silver staining.